Implementation of Trade Regulations on Fisheries to Prevent Fish Laundry in Indonesia - Ika Riswanti Putranti (Jurnal Hukum IUS QUIA IUSTUM, 2018)
Fish laundry or commonly known as fraud of fish origin or theft of fish in trade is to hide the origin and procedure of how fish is caught through unlawful processes such as IUU fishing or fisheries crime. The objective of this study was to answer two questions about: first, to what extent is the implementation of trade regulation in fisheries in order to prevent fish laundry in Indonesia and second, to analyze the shortcomings of Indonesia’s trade regulation in fisheries to prevent the penetration of fish laundry into domestic market. This was a normative study, using secondary data with statute approach, conceptual approach, and comparative approach, which was analyzed using descriptive qualitative approach. This study suggested that: first, fishery regulations are still focused on administrative procedures in disclosing the origin of fish, so that these are still less effective in preventing fish laundry. Second, the shortcoming of trade law is that it still prioritizes service function compared to supervision in fisheries, thus reducing the effectiveness of fish laundry monitoring